Thomas Arbousset and Francois Daumas in the Free State: tracing the exploratory tour of 1836 - Dreyer, J. (Southern African Humanities, 2021)
Arbousset and Daumas were pioneer missionaries of the Paris Evangelical Missionary Society who were sent to the country across the Orange River in 1833. In 1836 they undertook an extensive tour in the region now known as Lesotho and the Free State Province of South Africa. The report of their journey was published in 1846; only the second monograph to be published on Lesotho. The work became a seminal source on precolonial Basotho history, citing many landmarks and living places of groups occupying the interior. This paper attempts to trace the journey and to plot the sites as well as to identify the people mentioned; an attempt which proves successful in many cases, but in other cases indicates a need for further investigation. To cite this paper: Dreyer, J. 2001. Thomas Arbousset and Francois Daumas in the Free State: tracing the exploratory tour of 1836. Southern African Humanities 13: 61-96.